DLITE—An inexpensive, deployable interferometer for solar radio burst observations - Carson, George; Kooi, Jason E.; Helmboldt, Joseph F.; Markowski, Blerta B.; Bonanno, David J.; Hicks, Brian C. (Frontiers in Astronomy and Space Sciences, 2022)
Solar radio bursts (SRBs) are brief periods of enhanced radio emission from the Sun. SRBs can provide unique insights into the plasma structure where emission occurs. SRBs can also provide critical information concerning space weather events such as coronal mass ejections or solar energetic particle events. Providing continuous monitoring of SRBs requires a full network of detectors continuously monitoring the Sun. A promising new network is being developed, employing a four-element interferometer called the Deployable Low-band Ionosphere and Transient Experiment (DLITE) array. DLITE, which operates in a 30-40 MHz band, was specifically designed to probe the Earth’s ionosphere using high resolution measurements (1.024-second temporal resolution, 16.276-kHz frequency resolution); however, this also makes DLITE a powerful new tool for providing detailed observations of SRBs at these frequencies. DLITE is particularly adept at detecting long-duration SRBs like Type II and Type IV bursts. DLITE provides high resolution SRB data that can complement ground-based networks like e-Callisto or space-based observations, e.g., from Wind/WAVES. As an inexpensive interferometer, DLITE has strong potential as an educational tool: DLITE can be used to study the ionosphere, SRBs, and even Jovian radio bursts. Future DLITE arrays could be enhanced by using the full 20-80 MHz band accessible by the antennas and employing its millisecond time-resolution capability; this would improve DLITE's ability to track long-duration bursts, create the opportunity to study short-duration Type III bursts in detail, and, in particular, make the study of Type I bursts practical.